2011
DOI: 10.13060/00380288.2011.47.4.02
|View full text |Cite
|
Sign up to set email alerts
|

'Towards a Purer City': Problem Localities and Their Inhabitants from the Perspective of Local Authorities

Abstract: Drawing on the results of a qualitative study conducted in twelve Czech cities, the authors discuss how 'problematic localities' are represented in the narratives of local politicians and public offi cials. They analyse the ways in which these localities are categorised and how these categorisations are used to legitimise the specifi c treatment of these places and their inhabitants. City governance and administration are considered to be a part of a modern tradition of urban planning and city management, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…With regard to strategies to combat homelessness, outer actors often suggested rather vaguely that "someone has to solve the problem," not only because of public complaints but also owing to the negative image projected on Prague city center. The emphasis on the image and symbolic value of the city center that deserves protection and purification from the signs and "bearers" of visible marginalization was evident in the discourses of the outer municipal respondents (compare with MacLeod 2002; Vacková, Galčanová, and Hofírek 2011;Vašát 2012).…”
Section: Homelessnessmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to strategies to combat homelessness, outer actors often suggested rather vaguely that "someone has to solve the problem," not only because of public complaints but also owing to the negative image projected on Prague city center. The emphasis on the image and symbolic value of the city center that deserves protection and purification from the signs and "bearers" of visible marginalization was evident in the discourses of the outer municipal respondents (compare with MacLeod 2002; Vacková, Galčanová, and Hofírek 2011;Vašát 2012).…”
Section: Homelessnessmentioning
confidence: 99%
“…Using an interview design, Kostelecký, Patočková, and Illner (2012), for instance, concluded that the spatial concentration of socioeconomic problems in Prague, the Czechia, is relatively low and concentrated at the micro level (see also Sýkora 2009;. Thus, although social regeneration policies are rarely among the political priorities of government (Kostelecký, Patočková, and Illner 2012), the representation of "problematic neighbourhoods" in the narratives of local politicians and public officials has become evident in the "specific treatment" of certain cities and their inhabitants (Vacková, Galčanová, and Hofírek 2011). Such forms of applied institutional repression affect the daily practices and spatial mobility of the poorest class in urban areas (Vašát 2012), just as they affect other aspects of social behavior (e.g., Hejnal 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation